The Influence Of Coordination Team And Strategy Operational On Team Performance In Pacu Jalur With Change Management As A Mediating Variable - Ananda, Ragil; Nugroho, Gilang; Lubis, Rehansa (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
This study examines the influence of team coordination and operational strategy on team performance, with change management acting as a mediating variable, using the Alam Cahayo Tuah Nagori team in the Pacu Jalur competition as the research subject. Although previous studies have explored the relationship between coordination, strategy, and team performance, there is a gap in the literature that has not fully addressed how change management mediates this influence in the context of traditional sports undergoing professionalization. Using a quantitative approach and Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis, the study, involving a total of 80 respondents, finds that both team coordination and change management have a significant impact on team performance, while operational strategy does not show a direct significant effect. However, operational strategy is shown to have a significant indirect effect through change management, highlighting the critical role of change management in enhancing adaptability and team performance. These findings emphasize the importance of integrating team coordination, operational strategy, and change management to achieve optimal team performance, and contribute to the theoretical understanding of operational management in professionalized traditional sports. The study also provides practical implications for sports teams to enhance their effectiveness through adaptive change management in the dynamic context of competition.